Anti‐Angiogenic Properties of Cafestol and Kahweol Palmitate Diterpene Esters. Issue 12 (8th May 2016) - Moeenfard, Marzieh; Cortez, Alice; Machado, Vera; Costa, Raquel; Luís, Carla; Coelho, Pedro; Soares, Raquel; Alves, Arminda; Borges, Nuno; Santos, Alejandro
ABSTRACT: Epidemiological studies support the association of coffee‐specific diterpenes, with various beneficial health effects. Although anti‐antiangiogenic properties of free cafestol and kahweol have been recently described, available data regarding their esterified form, in particular palmitate esters as the main diterpene esters present in coffee, are still rare. Given that angiogenesis plays an important role in many pathological conditions, including cancer growth and metastasis, this study aimed to assess and compare the potential anti‐angiogenic effects of cafestol palmitate (CP) and kahweol palmitate (KP) in an in vitro angiogenesis model. According to our findings, both compounds inhibited angiogenesis steps on human microvascular endothelial cells (HMVECs), although a more significant effect was observed for KP. Compared to control, HMVECs viability decreased in a dose‐dependent manner upon incubation either with CP or KP. Concentrations of 75 and 100 μM of each compound were cytotoxic. Cell proliferation was also dramatically reduced by both diterpene esters at 50 μM, although KP had a stronger inhibitory effect. However, CP and KP did not induce apoptosis on HMVECs. Both compounds reduced cell migration, but this effect was only statistically significant after KP incubation. Inhibition of VEGFR2 expression and its downstream effector Akt, but not Erk, was also observed in CP‐ and KP‐treated HMVECs. These findings were confirmed using ELISA assay for phosphorylated (active) VEGFR‐2. Taken together, these data indicate that both CP and KP can be considered potent compounds against angiogenesis‐dependent disorders. Our findings further indicate that KP exerts more potent anti‐angiogenic effects than CP, in most of assays. J. Cell. Biochem. 117: 2748–2756, 2016. © 2016 Wiley Periodicals, Inc. Abstract : Our study shows that two diterpene compounds present in coffee are able to inhibit angiogenesis, namely by preventing proliferation, migration, and inducing apoptosis. We also show that these two molecules reduce VEGFR2 expression and activity and its downstream effector, Akt. These findings indicate that these two compounds can be used against angiogenesis‐associated disorders, like cancer, obesity, or diabetes vascular complications.